Rancang Bangun Sistem Pemberi Minum Lalat BSF (Black Soldier Fly) Otomatis Berbasis Mikrokontroler - Putri Utari; Ratna Aisuwarya; Resti Rahayu (Universitas Andalas, 2023)
The BSF fly (Black Soldier Fly) commonly known as the black soldier fly is an insect whose larvae are widely used as animal feed or commonly known as a maggot. BSF flies only need to drink, and do not eat. BSF fly feeding should be given regularly based on the ambient temperature around the cage. At this time, BSF fly breeders tend to have a busy and congested schedule so the cage spraying schedule is neglected. In addition, human negligence factors such as laziness and forgetting also make the spraying schedule irregular. Spraying of the cage was done manually using a plant sprayer. Therefore, research was conducted on the design of a microcontroller-based BSF fly drinking system. This system can perform automatic spraying of BSF flies based on the high and low temperatures around the cage, as well as provide notifications to the telegram of the BSF fly owner. Based on the study's results, this system detects the temperature around the cage using a DHT22 sensor and then sprays drinking BSF flies with the help of a DC pump. This system can be connected to the internet to send notifications that the cage has been sprayed via the telegram application of the cage owner.